The Current and Future Therapies of Bone Regeneration to Repair Bone Defects - Eijiro Jimi; Shizu Hirata; Kenji Osawa; Masamichi Terashita; Chiaki Kitamura; Hidefumi Fukushima (International Journal of Dentistry)
Bone defects often result from tumor resection, congenital malformation, trauma, fractures, surgery, or periodontitis in dentistry. Although dental implants serve as an effective treatment to recover mouth function from tooth defects, many patients do not have the adequate bone volume to build an implant. The gold standard for the reconstruction of large bone defects is the use of autogenous bone grafts. While autogenous bone graft is the most effective clinical method, surgical stress to the part of the bone being extracted and the quantity of extractable bone limit this method. Recently mesenchymal stem cell-based therapies have the potential to provide an effective treatment of osseous defects. In this paper, we discuss both the current therapy for bone regeneration and the perspectives in the field of stem cell-based regenerative medicine, addressing the sources of stem cells and growth factors used to induce bone regeneration effectively and reproducibly.